IMPLEMENTASI PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL MANADO-BITUNG DI KABUPATEN MINAHASA UTARA - Yandry Deby Ratu Rory; Charles R. Ngangi; Melsje Yellie Memah (Sam Ratulangi University, 2018)
This study aims to describe (1) implementation and (2) mechanism of land acquisition compensation for Manado-Bitung Toll Road development in North Minahasa Regency based on Law No. 2 Year 2012. The research was conducted on the object of Manado-Bitung Toll Road development of North Minahasa Regency. The study conducted from October 2017 to April 2018. The method used in this research is descriptive qualitative method. Determination of sample method used purposive sampling method. The research found that (1) in the process of land procurement implementation at the stages: (a) planning and (b) the preparation stage were not implemented properly. Initial data not available, multiple location revision fixes, and public consultations not implemented; (c) at the implementation stage by task force A and task force B are constrained by the absence of landowners, no land boundary markers, also at certain track terraces or point of the middle of the road there are coordinate differences, lack of building and plant appraisers, and land ownership issues; at stage (d) the delivery of the results has not yet been delivered as there are still areas ofland that have not been released yet. As for (2) The mechanism for appraisal of compensation is found in stage (a) Determination of Land Appraisal by the Chief of Land Acquisition Officer in the implementation of appraisal by appraissal person there is delay of nominative submission; at stage (b) deliberations that occurÂ are only limited to the determination of the form of indemnity and not the determination of the value of the indemnity. Whereas the determination of compensation value based on deliberation can prevent the occurrence of disagreement which will potentially the occurrence of dispute to the court can even cause riot, third stage (c) there is a consignment for compensation in court due to the existence of parcels that have no agreement in terms of the amount of compensation and still there dispute over land ownership.